The Influence of Board Diversity on Earnings Management in Non-Financial Companies in 2020-2023 - Iqbal, Muhammad; Zuraida, Zuraida; Mulyany, Ratna (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to investigate the impact of gender diversity, age diversity, independence, educational background diversity, and tenure diversity on earnings management in non-financial companies listed on the Indonesia Stock Exchange from 2020 to 2023. The sample includes non-financial companies listed before 2020 and remaining listed during the observation period. The sample selection was conducted using simple random sampling with Slovin's formula, resulting in 88 companies and 723 observations. The analysis shows that gender, age, independence, educational background, and tenure diversity reduce earnings management in non-financial companies listed on the Indonesia Stock Exchange from 2020 to 2023. These results imply that board diversity should be considered in shaping decisions and practices related to earnings management. Policies supporting diversity should be integrated into corporate governance strategies to enhance transparency, accountability, and reduce harmful earnings management practices.